CRIMINAL RESPONSIBILITY FOR PERSONNEL PERSONALITY DANGEROUS - Firman Wijaya (Awang Long Law Review, 2021)
The ability to be responsible (toerekeningsvatbaarheid) is Article 44 Paragraph (1) of the Criminal Code, which regulates a person 'sontoerekeningsvatbaarheidir’ responsible (matters). Perpetrators of dangerous personalities are perpetrators who are unable to take responsibility, so that their mental personality is disturbed by illness, their mental personality is in an unconscious state, and their mental personality is disabled in their growth. The personality of the soul makes it difficult for his actions to be held accountable for criminal law. The problem is is criminal liability for perpetrators of dangerous personalities? The research method is normative juridical research. The conclusion is that by determining whether there is a responsible capacity (toerekeningsvatbaarheid), that the judge must accept the results of the examination from a psychiatrist about the mental condition of the perpetrator of a crime, because it is the psychiatrist who has the competence to determine this. Then, based on the results of the examination, the judge determines the extent to which the mental condition of the perpetrator affects his actions, and then determines his ability to be criminally responsible for his actions. In the decision that the author is reviewing, namely Decision Number 144/Pid.B/2014/PN.Cj, it is stated that the defendant Pupun Bin Sanusi was legally and convincingly proven guilty of not committing the crime of "murder", but for this act he cannot be held accountable for any reason. forgiveness as intended in the provisions of Article 44 paragraph (1) of the Criminal Code.